Draft Annual Plan 1973-74 (Part-I-Notes) Union Territory of Pondicherry - Planning Commission (Planning Commission, 1973)
The Union territory of Pondicherry comprises the four regions of Pondicherry, Karaikal, Mahe and Yanam, covering an area of about 479,2 sq. kms. with a population of 4.71 lakhs, according to the provisional figures of the 1971 census. The Pondicherry region (area 290.1 sq. kms.) is on the east coast, about 160 kms. south of Madras. Pondicherry region is not a contiguous area but is inter-spersed with enclaves of Tamil Nadu. It consists of 267 villages, with a total population of 3.39 lakhs.
Revenue, Finance and Planning Department, Pondicherry